The Influence of Using Instagram as a Promotional Media in Building Brand Awareness and Its Impact on Purchase Decision of Bulog Products in Shopee - Freddy Pandapotan Simbolon; Ridha Ardyaningtyas Nurcholifa; Mouli Safarina (Bina Nusantara University, 2022)
In the digital era, social media increasingly has an important role as a marketing tool that needs to be optimized to increase a company’s sales and profitability. Social media continues growing and is widely used by all levels of society to become the appropriate media to offer products or services. The research aimed to test and prove the effect of social media marketing using Instagram on purchase decision through brand awareness for Bulog products in Shopee. The research used 397 respondents through purposive sampling with criteria of Instagram users who made transactions of Bulog products in Shopee during the last eight months. Data were collected using a questionnaire and distributed online through Google Form. Then, data were analyzed by Structural Equation Modeling - Partial Least Square (SEM-PLS) with WarpPLS 7.0. The results find that social media marketing through Instagram significantly influences brand awareness. It impacts the purchasing decisions at Perum Bulog in Shopee. Brand awareness also significantly influences purchase decision and mediates the effect of social media marketing on the purchase decision. Hence, companies must make social media the main tool for marketing programs. It can improve marketing personnel’s competence and creativity in creating marketing content on social media.